POLA KOMUNIKASI DOSEN DAN MAHASISWA TIMOR LESTE UNTUK MENINGKATKAN EFEKTIVITAS PEMBEAJARAN DI UNIVERSITAS TRIBHUWANA TUNGGADEWI - Leopoldino Soares; Herru Prasetya Widodo (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Communication is the basis for each individual to interact with the surrounding environment. Language differences become the background to the main problem for individuals to communicate with others. The purpose of this study is to know and understand the communication patterns of east Timor Timorens lectures and students to inprove the effectiveness of learning at UNITRI. This research is to examine and answer the objectives that have been determined by qualitative descriptive methods. In determining the informant, the research used purposive sampling technique. The conclusion is that primary, secondary, linear, and sircular communication pattners are the process of delivering messages by the giver to the recipient, symbolically this message gets motivation for students to improve effective communication patterns. There are two kinds of communication verbal and non-verbal communication. Verbal communication is the language/from of words, while non-verbal such as body language, facial expressions etc. but what happens to these students usually they use non-verbal communication as a process of young communication for them to interact with other people, lack of activity in a grup discussion. Keywords: Communication Patterns, Effectiveness, Learning Abstrak: Komunikasi merupakan dasar bagi setiap individu untuk berinteraksi dengan lingkungan sekitarnya. Perbedaan bahasa menjadi latar belakang permasalahan utama bagi individu untuk berkomunikasi dengan orang lain. Tujuan dari penelitian ini yaitu mengetahui dan memahami pola komunikasi dosen dan mahasiswa Timor Leste dalam meningkatkan efektivitas pembelajaran di UNITRI. Penelitian ini untuk mengkaji dan menjawab tujuan yang telah ditentukan dengan metode deskritif kualitatif. Dalam penentuan informan, peneliti mengunakan teknik purposive sampling. Kesimpulannya pola komunikasi primer, sekunder, linear, sirkular adalah proses penyampaian pesan oleh pemberi kepada penerima, secara simbol pesan ini mendapatkan motivasi bagi mahasiswa untuk meningkatkan pola komunikasi yang efektif. Ada dua macam komunikasi komunikasi verbal dan no-nverbal. Komunikasi verbal adalah bahasa/bentuk kata-kata, sedangkan non-verbal seperti bahasa tubuh, mimik wajah dll. Namun yang terjadi pada mahasiswa tersebut biasanya mereka mengunakan komunikasi non-verbal sebagai suatu proses komunikasi yang muda bagi mereka untuk berinteraksi dengan orang lain, kurangnya keaktif dalam berdiskusi kelompok. Kata Kunci: Pola Komunikasi, Efektivitas, Pembelajaran